Efficiency of Multi-Walled Carbon Nanotubes in Adsorbing Humic Acid from Aqueous Solutions - Moussavi, S.P.; Ehrampoush, M.H.; Mahvi, A.H.; Rahimi, S.; Ahmadian, M. (Asian Journal of Chemistry, 2014)
Presence of humic acid in water resources is one of health problems of most communities. Humic Acid naturally exists in water resources and is one of precursors of trihalomethanes (THMs). In recent years, various methods have been proposed to reduce or remove humic acid. This research was carried out with the aim of reviewing the feasibility of using multi-walled carbon nanotubes (MWCNTs) as an adsorbent to adsorb humic acid from aqueous solutions.This batch study was conducted under laboratory conditions including solution initial pH, contact time, different concentrations of humic acid and different adsorbent doses. Results were analyzed using SPSS and Excel software. Results revealed that as pH decreased, humic acid adsorption level increased. The highest adsorption level occurred at pH = 4. It was also observed that optimum time to achieve maximum adsorption of humic acid and to achieve equilibrium conditions was 3 h. As adsorbent dose increased, removal efficiency increased too and as initial concentration of humic acid decreased as well as humic acid removal efficiency increased. Owing to small size, large specific surface area, crystalline form, unique network order, high reactivity and good function of multi-walled carbon nanotubes as an adsorbent in removing organic pollutants from aqueous solutions, this adsorbent can be effective in removing humic acid.